Essential oil of Lepechinia schiedeana (Lamiaceae) from Costa Rica - Cicció, José F. (1999)
The composition of the essentiaí oil isolated by steam distillation from aerial parts of the Costa Rican herb Lepechinia schiedeana (Schlecht) Vatke (Lamiaceae) collected in El Empalme, Costa Rica, was determined by capillary gas chromatography (GC) and coupled gas chromatography-mass spectrometry (GCMS) analyses. Fifty-one components were identified corresponding ca. 93% of the oi!. The major components were -pinene (26.6%), cis -pinocamphone (25.1 %), &-3-carene (6.1 %), trans -pinocamphone (4.0%), camphor (3.8%) and